Ermeni Sorununda İki Ayrı Portre: Patrik Horen Aşıkyan ve Patrik Mateos İzmirliyan - Hale ŞIVGIN; Mehmet Batuhan ÇEKEN (Gazi Akademik Bakış)
The Armenian affair, which did not pose an internal problem for the Ottoman Empire until the middle of the 19th century, became an international problem, especially after the Bulgarian revolt of 1875. One of the articles of the Treaty of Berlin, signed as a result of the 1877-1878 Ottoman-Russian war, was the reform in the eastern provinces of the Ottoman Empire in the regions where Armenians lived. The Russian Czardom and the Western powers, especially Britain, began to pressure the Ottoman Empire over the affair of “Reform” and used the events carried out by separatist Armenian organizations such as the Hinchak and Dashnak committees as an intermediary. At this point, the committees, which understood the importance of mobilizing Armenians completely, wanted to use the Armenian Church, which had the most effective capacity to guide the Armenian people. For this, they pressured the people who were the Istanbul Armenian Patriarchs to make a choice and even assassinated Horen Aşıkyan, who did not help them. In this study, the differences between Patriarch Horen Aşıkyan, who is a supporter of the state and has a calming attitude in the face of rebel movements, and Mateos Izmirliyan, whose events in the opposite direction are provocative and uncompromising.